Effects of malic acid and citric acid on growth performance, antioxidant capacity, haematology and immune response of Carassius auratus gibelio. (21st April 2020) - Zhang, Lei; Zhang, Peijun; Xia, Changge; Cheng, Yi; Guo, Xiyao; Li, Yuehong
Abstract: The aim of this study was to investigate the effects of citric acid (CA) and malic acid (MA) on growth performance, antioxidant capacity, haematology and immune response of Carassius auratus gibelio . Carassius auratus gibelio were randomly divided into six groups, with three replicates in each group and 20 fish in each replicate. The six groups were fed a basic diet with organic acid supplementation (control group, 0.2%MA, 0.2%MA + 0.1%CA, 0.2%MA + 0.2%CA, 0.2%MA + 0.4%CA and 0.2%MA + 0.6%CA) for 8 weeks respectively. The results showed that compared with the control group, the weight gain rate and specific growth rate significantly increased in organic acid‐fed groups ( p  < .05). The highest value was in the 0.2%MA + 0.2%CA group. However, there were no significant differences in survival rate, red blood cells or white blood cells between groups. The contents of ALT, AST and LDH in Carassius auratus gibelio fed with organic acids increased, especially in 0.2%MA + 0.4%CA and 0.2%MA + 0.6%CA groups. However, there was no significant difference between the 0.2%MA + 0.2%CA group and the control group. In addition, the highest values of GSH and T‐AOC were found in the 0.2%MA + 0.6%CA group. Compared with the control group, there were no significant differences in the expression of HSP70 or LZM ( p  > .05), but the expression of Il‐1β, IL‐10 and TNF‐α was up‐regulated in the 0.2%MA + 0.4%CA and 0.2%MA + 0.6%CA groups. The results showed that the growth performance, antioxidant capacity, haematological parameters and expression of immune‐related genes were significantly improved by adding organic acids to the feed of Carassius auratus gibelio . However, excessive addition of organic acids may cause liver injury, and the optimal addition amount in this experiment was 0.2%MA + 0.2%CA.